ARTERIAL HYPERTENSION: BEHAVIORAL RISK FACTORS AMONG LITHUANIAN SEAMEN - Norkiene, S.; Dimaite, E. (European Scientific Journal, ESJ, 2014)
Aim: to determine the prevalence of hypertension among Lithuanian seamen and to evaluate its association with behavioral risk factors. Methods and results: A quantitative questionnaire survey was carried out with the aim to assess the behavioral risk factors for arterial hypertension. The study was carried out in Seamen’s Hospital, at the Marine Healthcare Centre. Data were analyzed by calculating the chi-square (χ²) value, the number of degrees of freedom (df), and the statistical significance (p). In 2012, elevated arterial blood pressure or hypertension was detected in 31.7% of seamen. The risk of arterial hypertension was related to the duration of smoking (p <0.01), body mass index (p <0.01), and age (p <0.001). In total, 50% of seamen with more than 15 years of smoking experience had elevated blood pressure. Every third (32.3%) seaman with overweight had elevated blood pressure, and one-half of seamen (50%) with obesity also had elevated blood pressure. Most seamen with AH grade I were >60 years of age or older. Conclusion. The risk of hypertension was associated with the duration of smoking experience (p<0.01) and body mass index (p <0.01). Associations with other behavioral risk factors were not statistically significant (p>0.05).